Roles of E3 ubiquitin ligases and deubiquitinating enzymes in renal cell carcinoma - Jiang, Minshu; Si, Wenxia; Huang, Sien; Qu, Sha; Zhang, Minghui; Quan, Yi (Frontiers in Oncology, 2026)
Ubiquitination is an important post-translational modification of proteins that precisely regulates protein stability and function through the coordinated actions of E3 ubiquitin ligases (E3s) and deubiquitinases (DUBs), participating in biological processes including protein degradation and signal transduction. In recent years, the role of ubiquitination modification in the carcinogenesis, progression, and treatment of renal cell carcinoma (RCC) has garnered increasing attention. This review summarizes the structural classifications of key enzymes in the ubiquitination process—E3s and DUBs—and to discuss their specific molecular mechanisms in RCC. Finally, we discuss the targeted therapeutic strategies focusing on these key ubiquitination-modifying enzymes in RCC.